2021
DOI: 10.1371/journal.pmed.1003778
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and costs associated with a lay counselor–delivered, brief problem-solving mental health intervention for adolescents in urban, low-income schools in India: 12-month outcomes of a randomized controlled trial

Abstract: Background Psychosocial interventions for adolescent mental health problems are effective, but evidence on their longer-term outcomes is scarce, especially in low-resource settings. We report on the 12-month sustained effectiveness and costs of scaling up a lay counselor–delivered, transdiagnostic problem-solving intervention for common adolescent mental health problems in low-income schools in New Delhi, India. Methods and findings Participants in the original trial were 250 school-going adolescents (mean [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…The current findings complement quantitative evidence from the host trial, which demonstrated significant and sustained advantages of the counsellor‐led intervention over 12 months (Malik et al, 2021 ; Michelson, Malik, Parikh, et al, 2020 ). The wider literature on low‐intensity interventions has also shown that human facilitation is associated with improved mental health outcomes and engagement over purely self‐directed formats (Bennett et al, 2019 ).…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…The current findings complement quantitative evidence from the host trial, which demonstrated significant and sustained advantages of the counsellor‐led intervention over 12 months (Malik et al, 2021 ; Michelson, Malik, Parikh, et al, 2020 ). The wider literature on low‐intensity interventions has also shown that human facilitation is associated with improved mental health outcomes and engagement over purely self‐directed formats (Bennett et al, 2019 ).…”
Section: Discussionsupporting
confidence: 79%
“…Our findings also raise the possibility that ultra‐brief human facilitation could offer incremental benefits over self‐help interventions that are completely self‐guided. Future work on low‐intensity interventions should examine other potentially resource‐efficient ways of providing human guidance, for example, through shared decision‐making protocols to decide on optimal dosing and blending human guidance with digital support (Gonsalves et al, 2021 ; Malik et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations